Madre e hijo, sombra y luz: La muerte de Raquel en el nacimiento de Benjamín según reescrituras de la temprana Edad Moderna - Grohsebner, Sabrina (Avisos de Viena, 2024)
A child comes into the world as his mother takes her last breath. Benjamin's first cry coincides with his mother Raquel's final words. Early modern poets and hagiographers draw upon this 'dual event' from Judeo-Christian tradition. Alonso Villegas, for instance, recounts it in his Flos Sanctorum. The birthing mother senses death looming over her. As she expires, she names her son, initially 'son of her pain', but Jacob rejects this somber name in favor of 'son of his right hand', signifying happiness. Benjamin's birth and Raquel's death epitomize maternal mortality, reflecting on birth as a moment of separation. Raquel's motherhood journey, marked by infertility struggles and finally fulfilled prayers, ends tragically with her death after giving birth to her second son. This study delves into the interplay of sorrow and love, loss and memory, and condemnation and divinization in Raquel's maternal experience.